Quality improvement through planned experimentation - Moen, Ronald D. (McGraw Hill, 1998)
This resource offers a comprehensive framework for the sequential building of knowledge -- a model for improvement -- that is key to making improvements. Step by step, you discover the tools and properties of sound experiments, the methods of planned experiments, and their application to the design of new and improved products and services.